Mengungkap Warisan Teks Islam Cirebon: Studi Filologis dan Katalogisasi Naskah Keraton Kanoman - Ihsan Sa'dudin (Matan : Journal of Islam and Muslim Society, 2025)
The Kanoman Palace of Cirebon preserves a number of religious manuscripts written in Arabic, Javanese, Pegon, and Malay, most of which have not been properly inventoried. The absence of a manuscript catalog limits researchers’ access and negatively affects preservation efforts, especially since many of the manuscripts have suffered physical deterioration. This study aims to carry out a systematic cataloging of the manuscripts as a strategic step toward their preservation through digitalization, codicological identification, and the preparation of detailed manuscript descriptions. The research employs philological methods with a focus on codicology, including analyses of writing materials, dimensions, pagination, physical condition, script, language, ink, illumination, rubrication, and textual content. The findings reveal that 22 manuscripts were successfully inventoried, consisting of 15 Arabic-language manuscripts and 7 manuscripts written in non-Arabic languages. The primary themes represented in the collection include Sufism, Islamic jurisprudence (fiqh), theology (tawhid), Arabic grammar (nahwu), and morphology. The cataloging process produced comprehensive codicological data that highlight the condition of the manuscripts, many of which exhibit damage such as tears, holes, or fading ink. This study affirms that cataloging is an effective preservation measure because it provides accurate access to information without requiring direct physical contact with manuscripts that are vulnerable to further damage. Moreover, the research opens new avenues for subsequent manuscript studies, particularly in the effort to preserve Cirebon’s cultural and intellectual heritage.